2023
DOI: 10.1536/ihj.22-379
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001312 Silencing Suppresses Doxorubicin-Induced Cardiotoxicity via MiR-409-3p/HMGB1 Axis

Abstract: Doxorubicin (DOX) is a potent cytotoxic chemotherapeutic agent limited in clinical application owing to its cumulative and irreversible cardiotoxicity. Circ_0001312 is highly expressed in patients with heart failure. However, it is still unclear whether circ_0001312 plays any roles in DOX-induced cardiotoxicity.Human AC16 cardiomyocytes in functional group were stimulated with DOX. The levels of genes and proteins were detected by qRT-PCR and western blotting. The proliferation, apoptosis, as well as inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…miR-409-3p can target high-mobility group box 1 (HMGB1), thereby reducing DOX-induced myocardial cell apoptosis. This further confirms the regulatory role of circRNA_0001312 in the process of DOX-induced myocardial cell injury [ 139 ].…”
Section: Drug Side Effectssupporting
confidence: 80%
“…miR-409-3p can target high-mobility group box 1 (HMGB1), thereby reducing DOX-induced myocardial cell apoptosis. This further confirms the regulatory role of circRNA_0001312 in the process of DOX-induced myocardial cell injury [ 139 ].…”
Section: Drug Side Effectssupporting
confidence: 80%
“…Although we acknowledge limitations such as sample variation and the need for further validation, our findings will greatly enhance our understanding of circRNA function and its potential implications in heart development and maturation in large mammals. It was reported that modulating the expression of circRNAs confers cardioprotection in preclinical animal models of heart failure (19,64,65). In this study, we identified and validated six circRNAs that regulate cardiomyocyte cell cycle and proliferation.…”
Section: Discussionmentioning
confidence: 85%
“…Human AC16 cardiomyocytes were obtained from ATCC (Rockville, MD, USA) and maintained in Dulbecco's modified Eagle medium (Gibco, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (Gibco) and 1% penicillin-streptomycin (Gibco) in a humidified atmosphere at 37°C with 95% air and 5% CO 2 . To induce a myocardial cell injury model, AC16 cells were treated with 5 μM DOX (Sangon Biotech Co., Ltd., Shanghai, China) for 24 h. 17 In some experiments, AC16 cells were treated with 5 μM DOX for different periods (0, 0.5, 2, 6, 12, 24, and 48 h) for the detection of RNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…Para induzir um modelo de lesão celular miocárdica, as células AC16 foram tratadas com 5 μM de DOX (Sangon Biotech Co., Ltd., Xangai, China) por 24 horas. 17 Em alguns experimentos, as células AC16 foram tratadas com 5 μM de DOX por diferentes períodos (0, 0,5, 2, 6, 12, 24 e 48 h) para detecção da expressão de RNA.…”
Section: Materiais E Métodosunclassified